REVITALISASI ZAKAT DAN WAKAF SEBUAH SOLUSI KEMISKINAN DI INDONESIA - Syukri Iska (JURIS (Jurnal Ilmiah Syariah), 2020)
Islamic community is always identical with poverty. This reality seems cannot be ignored. The fact shows that most of poverty countries come from Islamic communty. Indonesia as a developing country is one of poverty countries. It has a lot of Moslems. However, these are many problem appear, such as inflation, depreciation, education, and health problem. As a matter of fact, Islam apposes poverty there are many ayats and hadits (prophet’swords) state the danger of poverty. This danger can threat individual as well as community. And, it can also threat belief, faith, moral, throught, and culture.